Impacts and Challenges Associated With Shrimp Cultivation in Parulia Union, Satkhira, Bangladesh: an Empirical Study - Prodhan, Shamima; Sikder, Bivuti Bhushan; Nasreen, Mahbuba (Journal of the Asiatic Society of Bangladesh, Science, 2019)
This paper offers an overview of an empirical study conducted at Parulia union in Satkhira district, Bangladesh on unplanned shrimp culture, practiced by masses that ultimately led to serious environmental degradation and socioeconomic consequences such as salinity intrusion, decline in water and soil qualities, reduction in agricultural productions, decrease in cattle production, migration, and human health hazards. The real scenarios give evidences of the impacts of imposed shrimp cultivation and the associated challenges faced by the communities including reduction in cultivable land area (59.8%), increase of Gher area (48.0%), increase of soil salinity (74.5%), reduction in vegetable production (67.6%), reduction in agriculture farming (67.6%), reduction in freshwater fish culture (63.7%), impacts on livelihood patterns and reduction in local varieties of crops, fruit trees, and plants. Major challenges identified by the respondents are: reduction in soil quality (41.2%), reduction in water quality (38.2%), social problems (20.6%), problems in getting safe drinking water (19.6%), landlessness (35.3%), migration (34.4%), outbreak of common diseases (19.6%) etc. Urgency of a national policy framework addressing the issue holistically is of grave importance to solve the problem. Asiat. Soc. Bangladesh, Sci. 45(1): 55-69, June 2019